2023
DOI: 10.1111/jopy.12866
|View full text |Cite
|
Sign up to set email alerts
|

Differential responses to ethical vegetarian appeals: Exploring the role of traits, beliefs, and motives

Abstract: ObjectiveThis research examines differential responses to ethical vegetarian appeals as a fuction of individuals' personalities.BackgroundEthical vegetarian appeals are persuasive messages promoting the adoption of a plant‐based diet on moral grounds. Individuals may vary in their receptivity to such appeals, depending on their morally relevant traits (e.g., agreeableness), beliefs (e.g., speciesism), and motives (e.g., concerns about animal welfare).MethodsWe explored (Study 1, N = 907) and then attempted to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 68 publications
2
5
0
Order By: Relevance
“…First, there are main effects of personality traits on morally relevant outcomes (Hopwood et al, 2024;Pringle et al, 2024;Wilks et al, 2024;Zher-Wen et al, 2024) that do not necessarily interact with situational factors (Thielmann et al, 2024). Second, the effect of situational influences may depend on personality traits (Smillie et al, 2024). Third, the effect of personality traits on outcomes may depend on the context (Hudson & Uenal, 2024).…”
Section: The Power Of Personalitymentioning
confidence: 99%
See 3 more Smart Citations
“…First, there are main effects of personality traits on morally relevant outcomes (Hopwood et al, 2024;Pringle et al, 2024;Wilks et al, 2024;Zher-Wen et al, 2024) that do not necessarily interact with situational factors (Thielmann et al, 2024). Second, the effect of situational influences may depend on personality traits (Smillie et al, 2024). Third, the effect of personality traits on outcomes may depend on the context (Hudson & Uenal, 2024).…”
Section: The Power Of Personalitymentioning
confidence: 99%
“…Likewise, applying this framework to the study of moral personality, McAdams and Mayukha (2024) propose that we can conceive of morality in terms of (1) moral traits, (2) values and moral reasoning, and (3) an integrative moral life story. Adopting a similar integrative approach, Smillie and colleagues (2024) assess different kinds of personality constructs—traits, beliefs, and motives—that might capture differential responses to ethically framed messages promoting plant‐based diets.…”
Section: Contributions Of Personality Psychologymentioning
confidence: 99%
See 2 more Smart Citations
“…This could help uncover which campaigns are most practically effective and could guide bespoke initiatives and campaigns, rather than trying a 'one size fits all' approach. For example, recent work by Smillie and colleagues with adults in Australia, Canada, New Zealand, the UK, and the USA found that persuasive messaging promoting the adoption of plant-based diets to reduce one's carbon footprint was more effective for people who scored higher on the personality trait of openness/intellect [55].…”
Section: Future Researchmentioning
confidence: 99%